The role of corneal biomechanics in visual field progression of primary open-angle glaucoma with ocular normotension or hypertension: a prospective longitude study - Wei, Yahui; Cai, Yu; Bao, Chenying; Zhu, Yanfei; Pan, Yingzi (Frontiers in Bioengineering and Biotechnology, 2023)
[Introduction]: To analyze effects of dynamic corneal response parameters (DCRs) on visual field (VF) progression in normal-tension glaucoma (NTG) and hypertension glaucoma (HTG). [Methods]: This was a prospective cohort study. This study included 57 subjects with NTG and 54 with HTG, followed up for 4 years. The subjects were divided into progressive and nonprogressive groups according to VF progression. DCRs were evaluated by corneal visualization Scheimpflug technology. General linear models (GLMs) were used to compare DCRs between two groups, adjusting for age, axial length (AL), mean deviation (MD), etc. VF progression risk factors were evaluated by logistic regression and receiver operating characteristic (ROC) curves. [Results]: For NTG, first applanation deflection area (A1Area) was increased in progressive group and constituted an independent risk factor for VF progression. ROC curve of A1Area combined with other relevant factors (age, AL, MD, etc) for NTG progression had an area under curve (AUC) of 0.813, similar to the ROC curve with A1area alone (AUC=0.751, P=0.232). ROC curve with MD had an AUC of 0.638, lower than A1Area-combined ROC curve (P=0.036). There was no significant difference in DCRs between the two groups in HTG. [Conclusion]: Corneas in progressive NTG group were more deformable than nonprogressive group. A1Area may be an independent risk factor for NTG progression. It suggested that the eyes with more deformable corneas may also be less tolerant to pressure and accelerate VF progression. VF progression in HTG group was not related to DCRs. Its specific mechanism needs further studies.